West Bank and Gaza : Area C and the future of the Palestinian economy - World Bank. Poverty Reduction and Economic Management Department (Palestine World Bank, 2013)
This report examines the economic benefits of lifting the restrictions on movement and access as well as other administrative obstacles to Palestinian investment and economic activity in Area C.
Acronyms and abbreviations -- Acknowledgments -- Executive summary -- Chapter 1: The Palestinian economy, Israeli restrictions and the potential of Area C -- Chapter 2: Area C - output potential of key sectors of the Palestinian economy : I. Agriculture -- II. Dead Sea minerals -- III. Stone mining and quarrying -- IV. Construction and real estate -- V. Tourism and the Dead sea -- VI. Telecommunications -- VII. Cosmetics -- Chapter 3: Indirect beneficiaries
Includes bibliographical references (p.51-52)
Keywords: Economic development; ECONOMIC FORECASTS; ECONOMIC DEVELOPMENT; ECONOMIC CONDITIONS; PALESTINE